PENGARUH PERBANDINGAN EKSTRAK KULIT PISANG DENGAN GELATIN TERHADAP KUALITAS SOFT CANDY KULIT PISANG - Rudi Hidayat (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2020)
Banyuwangi has many banana-based food product, so everyday producing abundant of banana peels waste. Therefore to utilize the peels waste can use in making soft candy. The aim of this study was to know the effect of banana peels extract addition of soft candy on quality (chemical and hedonic) of soft candy and to determine the comparison between banana peels and gelatin in making the best soft candy. This research evaluated the comparison of banana peels and gelatin in producing soft candy. Experimental design used was completely randomized design with 4 treatments in comparison of banana peels and gelatin namely banana peels : gelatin (0:1) (K1), banana peels : gelatin (1:1) (K2), banana peels : gelatin (1:2) (K3), banana peels : gelatin (2:1) (K4).